Application of continuous quality improvement for gastric cancer patients undergoing tube feeding at home (持续质量改进在胃癌家庭管饲管理中的应用) - ZHOU Yuzhen (周玉珍); LIN Youyan (林友燕); YU Xinyan (俞新燕) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of continuous quality improvement for gastric cancer patients undergoing tube feeding at home. Methods A continuous quality improvement program had been carried out since May, 2020. The correct rate of tube feeding at home and compliance with the home enteral nutrition before implementation of continuous quality improvement (from November 2019 to April 2020) and after implementation of continuous quality improvement (from May 2020 to October 2020) were compared. Results The correct rate of tube feeding at home increased from 88. 89% before intervention to 97. 78% after intervention, and the rate of compliance with the home enteral nutrition increased from 77. 78% before intervention to 93. 33% after intervention. Conclusion Application of continuous quality improvement is effective to improve compliance with tube feeding at home for gastric cancer patients. (目的 探讨持续质量改进在胃癌家庭管饲管理中的应用效果。方法 2020年5月开始实行持续质量改进, 比较持续质量改进前(2019年11月-2020年4月治疗的45例胃癌家庭管饲患者)和改进后(2020年5月-10月治疗的45例患者)的家庭管饲正确率和肠内家庭营养依从性。结果 干预后家庭管饲正确率由干预前的88. 89%上升为97. 78%, 家庭肠内营养依从性由干预前的77. 78%提高为93. 33%。结论 持续质量改进能有效提高胃癌患者家庭管饲正确率和依从性。)